Lineage Compatibility (Kafa’ah Nasab) in the Marriage of Sayyid and Syarifah: Between Tradition and Modernity (A Study on the Polewali Mandar Branch of Rabithah Alawiyyah) - Istiqamah, Intan; Budiman, Budiman; Aris, Aris; Mutmainnah, Iin; Abd. Karim Faiz; Makmur, Makmur (State Islamic University Datokarama Palu, 2025)
Kafa'ah means being equal, balanced, and compatible. This abstract discusses the importance of the principle of Kafa'ah in marriage, particularly in the context of choosing a spouse who is compatible in social, moral, and economic aspects. Kafa'ah is recognized by scholars from the four Islamic schools of thought, each with different views on its application. The Hanafi, Maliki, Shafi'i, and Hanbali schools emphasize different aspects of religion, lineage, social status, and economics. The author also highlights the practice of Kafa'ah among the Habaib (Ahlul Bayt), especially in preserving the lineage of the Prophet Muhammad, where a Syarifah is expected to marry a Sayyid to maintain the family lineage. Although Kafa'ah in marriage aims to preserve household harmony, marriages are still considered valid even if the couple is not equal in lineage. In Indonesia, organizations like Rabithah Alawiyyah play an important role in preserving the traditions and welfare of the Alawiyyin community, including in matters of Kafa'ah lineage. This research examines the views of the Habaib on Kafa'ah lineage as a primary condition for the marriage of Sayyid and Syarifah.